Topside Ionospheric Electron Temperature Observations of the 21 August 2017 Eclipse by DMSP Spacecraft. Issue 15 (30th April 2018) - Hairston, Marc R.; Mrak, Sebastijan; Coley, W. R.; Burrell, Angeline; Holt, Ben; Perdue, Michael; Depew, Matthew; Power, Robert
Abstract: During the 21 August 2017 eclipse two separate DMSP spacecraft passed through the lunar penumbra at local afternoon (F16) and near local sunset (F17) in the topside ionosphere at an altitude of 850 km. Measurements of the in situ electron temperature by the Langmuir probe on each spacecraft showed regions where the temperature decreased on the order of 500 to 1, 000 K in the shadow. The patterns of these decreases were sporadic inside the shadow but generally showed the same overall shape in both passes. Comparing these patterns of temperature reductions with the projection of the gradient of the solar EUV radiation in the ionosphere suggests that these complex patterns are a result of the nonuniform distribution of the solar EUV radiation on the Sun at the time of the eclipse. Plain Language Summary: As the shadow of the Moon moves across the Earth's upper atmosphere, the decrease in ultraviolet light from the Sun causes a cooling of the electrons in the ionosphere. Measurements during the 21 August 2017 eclipse from the DMSP spacecraft showed a complex and puzzling pattern of this temperature drop. The uneven distribution of the ultraviolet light sources from active regions on the Sun's surface is suggested as a possible explanation. Key Points: Two DMSP spacecraft passing through the 21 August 2017 eclipse shadow detected decreases in the electron temperature in topside ionosphere The shapes of these decreases in the electron temperature were complex but showed a repeated pattern that was seen by both spacecraft The sporadic temperature decreases can best be explained by the nonuniform EUV solar illumination of the ionosphere during the eclipse